The Impact of Financial Influencers, Social Influencers, and FOMO Economy on the Decision-Making of Investment on Millennial Generation and Gen Z of Indonesia - Martaningrat, Nike Wahyu Suci; Kurniawan , Yohannes (Journal of Ecohumanism, 2024)
This study aims to observe the impact of financial influencers, social influencers, and the FOMO economy moderated by financial behavior and financial literacy on the decision-making to invest in the millennial generation and Gen Z of Indonesia. This study used a Likert scale questionnaire to collect the data. There were 306 samples gathered. The data were analyzed using Smart PLS software with the PLS method. The result showed that the financial influencers and the FOMO economy significantly influenced investment decision-making for the Millennial and Generation Z generations. However, when financial influence as a variable when moderated either by financial literacy or by financial behavior, it would become less significant in influencing investment decision-making for the Millennial and Generation Z generations. In contrast, social influence was not significantly influencing investment decision-making for the Millennial and Generation Z generations. However, after the variable social influence moderated by financial literacy or financial behavior, the social influence effect had a significant impact on investment decision-making. On the other hand, the FOMO economy as a variable after being moderated by financial literacy or financial behavior has a significant impact on investment decision-making.